Adopsi Energi Hijau Berbasis Panel Surya Untuk Menghemat Biaya Operasional Pada Irigasi Pertanian - Sudianto; Ajeng Dyah Kurniawati (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
The problem of farmer groups in Kedungbenda Village is the constraints of the planting cycle, which is limited to only twice a year due to drought on agricultural land. So far, irrigation has been sustained from rainfall. As a result, farmers supply irrigation by pumping water from rivers. However, it costs a lot of money. This activity aims to apply solar panel-based green energy to overcome operational costs in agricultural irrigation experienced by farmer group partners in Kedungbenda Village, Purbalingga. The approach used in this activity is the installation of solar panel-based Appropriate Technology (TTG) tools. The output target of this activity is that solar panels are installed and function to pump water as a saving on agricultural irrigation operations. TTG Solar panels can reduce operational costs for farmer groups by up to 90%. In addition, the sustainability of this activity is expected to help farmer groups in Kedungbenda Village in agricultural irrigation by irrigating rice fields without electricity and diesel costs. In addition, this activity can help farmer groups during droughts in the rice fields of Kedungbenda Village.